SCREENING AND SIGNALLING NON-COGNITIVE SKILLS: EXPERIMENTAL EVIDENCE FROM UGANDA∗ - Bassi, Vittorio; Nansamba, Aisha (Oxford University Press, 2022)
We study how employers and job seekers respond to credible information on skills that are difficult to observe, and how this affects matching in the labour market. We experimentally vary whether certificates on workers’ non-cognitive skills are disclosed to both sides of the market during job interviews between young workers and small firms in Uganda. The certificates cause workers to increase their labour market expectations, while high-ability managers revise their assessments of the workers’ skills upwards. The reaction in terms of beliefs leads to an increase in positive assortative matching and to higher earnings for workers, conditional on employment.